Chemical Production Fault Detection Technology Based on Computer Process Control Software - Jun Han (Chemical engineering transactions, 2017)
Chemical production safety is the only way to ensure the economic benefits and development and the life safety of employees in a company. For any company, the safety production is a subject which cannot be ignored. To get early warning of the potential risks, the troubleshooting technology in the process of chemical production is no doubt vital to the modern business. For this purpose, this paper, by ways of literature investigation, comparative analysis and case analysis, and on account of chemical fault detection mechanism model, proposes a chemical production fault detection model with process simulation based on computer process control software. In the other way, the availability and the feasibility of the model also have a sound verification with simulation case analysis.